Current Issues in Implementing Project-Based Learning in Higher School (The Materials of the Round-Table Discussion) - M. V. Pevnaya; L. N. Boronina; A. V. Kulminskaia (Высшее образование в России)
The integration of project-based learning into higher education is a topic of significant interest to scholars and practitioners from different countries. As part of the X International Scientific and Practical Conference ‘Strategies for the Development of Social Communities, Institutions and Territories’ on 18 April 2024, the Ural Federal University hosted a round table ‘Project Based Learning: Interdisciplinary and Organisational Context, Partnership Opportunities’. Researchers and managers representing 12 Russian universities took part in the scientific discussion. The round-table discussion highlighted a number of pertinent research questions that require critical evaluation by researchers of higher education and the academic community responsible for the transformation of the academic environment, the educational process, and educational activities. The relevant research was analyzed, and it was found that there were two main areas of focus: 1) the integration of project learning into the educational process and extracurricular activities in higher education; 2) the partnership of Russian universities with external project customers and the formation of a culture of interaction in the implementation of project learning.